2020
DOI: 10.3389/fmed.2020.00101
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Skin Microbiome and Skin Physiological Functions Between Bedridden Older Patients and Healthy People: A Single-Center Study in Japan

Abstract: With the increase in the older populations, the number of bedridden older patients is becoming a matter of concern. Skin microbiome and skin physiological functions are known to change according to lifestyle and community; however, such changes in case of movement-and cleaning-restricted bedridden older patients have not yet been revealed. To address this issue, we analyzed skin microbiome and skin physiological functions, including pH, hydration, sebum level, and transepidermal water loss (TEWL), of bedridden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 62 publications
1
58
0
Order By: Relevance
“…PERMANOVA, SIMPER, and PAM clustering analyses have been used in a variety of studies [ 32 34 ]. In the current study, the differences in bacterial communities between the MSC and CCl 4 groups at designated times (i.e., 48 h, 1 w, and 2 w) were determined by the three analyses, and the relevant results showed the largest difference between the MSC and CCl 4 groups occurred at 48 h. As the most obvious difference of survival percentages of mice between the MSC and CCl 4 groups occurred from 48 h to 1 w, it implied that the change of intestinal bacterial communities was associated with this obvious difference.…”
Section: Discussionmentioning
confidence: 99%
“…PERMANOVA, SIMPER, and PAM clustering analyses have been used in a variety of studies [ 32 34 ]. In the current study, the differences in bacterial communities between the MSC and CCl 4 groups at designated times (i.e., 48 h, 1 w, and 2 w) were determined by the three analyses, and the relevant results showed the largest difference between the MSC and CCl 4 groups occurred at 48 h. As the most obvious difference of survival percentages of mice between the MSC and CCl 4 groups occurred from 48 h to 1 w, it implied that the change of intestinal bacterial communities was associated with this obvious difference.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by Nagase et al (2020), the sacral region, where PIs frequently occur, was found to be contaminated with gut-related bacteria such as Bacteroides species (spp. ), Enterococcus spp., and Klebsiella spp.…”
mentioning
confidence: 94%
“…), Enterococcus spp., and Klebsiella spp. Moreover, the wound microbiome just after PI occurrence was very close to the skin microbiome around the PI, implying that the underlying skin microbiome may be a cause of wound infection (Konya et al, 2005; Nagase et al, 2020; Smith et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations